Volatile pheromone signalling in Drosophila - Smith, Dean P. (2012)
Once captured by the antenna, 11-cis vaccenyl acetate (cVA) binds to an extracellular binding protein called LUSH that undergoes a conformational shift upon cVA binding. The stable LUSH–cVA complex is the activating ligand for pheromone receptors present on the dendrites of the aT1 neurones, comprising the only neurones that detect cVA pheromone. This mechanism explains the single molecule sensitivity of insect pheromone detection systems. The receptor that recognizes activated LUSH consists of a complex of several proteins, including Or67d, a member of the tuning odourant receptor family, Orco, a co-receptor ion channel, and SNMP, a CD36 homologue that may be an inhibitory subunit. In addition, genetic screens and reconstitution experiments reveal additional factors that are important for pheromone detection. Identification and functional dissection of these factors in Drosophila melanogaster Meigen should permit the identification of homologous factors in pathogenic insects and agricultural pests, which, in turn, may be viable candidates for novel classes of compounds to control populations of target insect species without impacting beneficial species.